KEANEKARAGAMAN JENIS DAN KONDISI EKOSISTEM PADANG LAMUN PANTAI GEGER, NUSA DUA, BALI - Windy Naibaho; I Wayan Arthana, Ni Luh Gede Rai Ayu Saraswati (ADISAM PUBLISHER, 2025)
This study aims to analyze the species diversity, density, coverage, and environmental conditions of seagrass beds at Geger Beach, Nusa Dua, Bali. The method used is quantitative descriptive, with field data collection through line transects and quadrats, as well as analysis of physical, chemical, and biological parameters. The results show the presence of six dominant seagrass species, namely Cymodocea rotundata, Thalassia hemprichii, Syringodium isoetifolium, Halophila ovalis, Halodule uninervis, and Halodule pinifolia. The highest density values were found in Cymodocea rotundata and Syringodium isoetifolium, with a total density reaching 1,119 stands/m². The average seagrass coverage was 39.83%, classified as moderate but still considered to be in an unhealthy condition. The diversity index was in the moderate category (1.37–1.45), evenness was high (0.76–0.81), and dominance ranged from low to moderate (0.25–0.31). Water quality parameters such as temperature, pH, dissolved oxygen, salinity, and turbidity were still within the range that supports seagrass growth. In addition, five types of associated fauna (megabenthos) were found coexisting with the seagrass. This study emphasizes the importance of conserving seagrass beds as productive habitats and living spaces for various marine species